WEAI-Climate Stakeholder Consultation Workshop - Bryan, Elizabeth; Magalhaes, Marilia; Go, Ara; Malapit, Hazel J. (International Food Policy Research Institute, 2023)
The Methods Module of the CGIAR GENDER Impact Platform convened a group of experts on climate change and gender from CGIAR and partner organizations at a workshop held in Washington, DC, November 9-10, 2023. The goal of the workshop was to identify measurement gaps and best practices to support the development of a new tool for measuring women’s empowerment in the context of climate change and resilience. This new tool will complement the existing project-level Women’s Empowerment in Agriculture Index (pro-WEAI) and will be developed and piloted in collaboration with IFPRI’s Gender, Climate Change and Nutrition Integration Initiative (GCAN) over the next two years.